Real-world disability improvement in patients with relapsing–remitting multiple sclerosis treated with natalizumab in the Tysabri Observational Program. (April 2021) - Wiendl, Heinz; Spelman, Tim; Butzkueven, Helmut; Kappos, Ludwig; Trojano, Maria; Su, Ray; Campbell, Nolan; Ho, Pei-Ran; Licata, Stephanie
Background: Natalizumab has been associated with disability improvement as indicated by a confirmed Expanded Disability Status Scale (EDSS) score decrease. Objective: The aim of this study was to characterize disability improvement in patients in the Tysabri Observational Program (TOP), an ongoing observational study of relapsing–remitting multiple sclerosis patients initiating natalizumab in clinical practice. Methods: TOP data as of November 2018 were included. Confirmed disability improvement (CDI) was defined as a decrease ⩾1.0 confirmed 24 weeks later from a baseline EDSS score ⩾2.0. Confirmed functional system (FS) improvement was defined as a decrease ⩾1.0 confirmed 24 weeks later from a baseline score ⩾1.0 in that FS. Results: Of 5384 patients, 1287 (23.9%) had CDI; 51.8% experienced CDI in the first treatment year. Among patients with CDI, 56.6% had CDI ⩾1.5 points; 34.4% had CDI ⩾2.0 points. The cumulative probability of maintaining improvement 8 years after the CDI event was 52.6%. At treatment initiation, 5363 patients (85.2%) had impairment in ⩾1 FS. At 8 years, the cumulative probability of confirmed improvement in any FS was 88.8% and ranged from 38.3% to 58.6% in individual FS. Conclusion: These results highlight disability improvement as a potential benefit of natalizumab treatment. Improvements across all FS demonstrate the range of functional improvement.